Do Clinical Death and Resuscitation Make an Organism Healthier? Paradox in Medical Statistics - P. P. Zolin (Вестник анестезиологии и реаниматологии)
The objective: to trace changes in endotoxicosis in the brain during the postresuscitation period.Subjects and Methods. Clinical death was modeled on rats by 6.5-minute asphyxia and resuscitation.The animals were divided into groups corresponding to the timing of brain sampling (from 30 minutes to 21 days) after resuscitation. The content of low and median molecular weight substances (LMMWS) was determined in perchloric acid extracts of the brain.Results. It was found that 30 minutes after resuscitation the content of LMMWS in the brain of rats increases statistically significantly compared to the "control" group, and after 90 minutes returns to the control level. Then, 6 hours – 21 days after resuscitation a paradoxical decrease in the content of LMMWS below the control level occurs.Conclusion. The decrease in the level of endotoxicosis after asphyxia and resuscitation explains not by their “healing” effect, but by the death of rats with the highest LMMWS values, which leads to a decrease in the average LMMWS value in groups of resuscitated animals.